Development of Pocket Book of Tissue Culture Based on Case Method - Harahap, Fauziyah; Sihombing, Josephine Gloria Margareth; Suriani, Cicik; Nusyirwan, Nusyirwan; Edi, Syahmi; Daulae, Abdul Hakim; Nursamsu, Nursamsu (Biosfer: Jurnal Tadris Biologi, 2023)
The use of pocket book as a learning media is still limited. This will make it difficult for students to understand the material. The purpose of this research was to determine the feasibility results of tissue culture pocket book, the level of product feasibility through responses from lecturers, students and to see the effectiveness of tissue culture pocket book products especially in tool sterilization and in vitro propagation topics. The research method uses R&D with 4D models from Thiagrajaan. The results of the needs analysis showed that 66,7% of students had difficulty in understanding the material of tool sterilization and in vitro propagation. In curriculum analysis using the KKNI curriculum. The feasibility level of the assessment product from media experts obtained the criteria "Very worthy" with percentage of 91,67%, assessment of material experts with the criteria "worhty" with percentage of 84,74% and assessment results of learning design experts with the criteria "Very worthy" with percentage of 91,67%. Then the lecturer's response obtained results with the criteria "Worthy" with a percentage of 83,75%. In small group trials with scores of 89.4% and limited field trials of 90%. The disseminate stage obtained an N-Gain score of 0,56 with the "medium" criteria. ABSTRAK: Penggunaan buku saku sebagai media pembelajaran masih terbatas. Hal ini akan menyulitkan mahasiswa dalam memahami materi pembelajaran. Tujuan dari penelitian ini adalah untuk mengetahui hasil kelayakan buku saku kultur jaringan, tingkat kelayakan produk melalui tanggapan dari dosen, mahasiswa dan untuk melihat efektivitas produk buku saku kultur jaringan khususnya pada topik sterilisasi alat dan perbanyakan in vitro. Dalam penelitian ini menggunakan R&D dengan model 4D Thiagrajaan. Hasil analisis kebutuhan menunjukkan bahwa 66,7% mahasiswa mengalami kesulitan dalam memahami materi sterilisasi alat dan propagasi in vitro. Kurikulum yang digunakan adalah KKNI. Tingkat kelayakan produk penilaian dari ahli media diperoleh hasil dengan kriteria "Sangat layak" dengan persentase 91,67%, penilaian ahli materi dengan kriteria "Layak" dengan persentase 84,74% dan hasil penilaian ahli desain pembelajaran dengan kriteria "Sangat layak" dengan persentase 91,67%. Kemudian respon dosen diperoleh hasil dengan kriteria "Layak" dengan persentase 83,75%. Dalam uji coba kelompok kecil diperoleh skor 89,4% dan uji coba lapangan terbatas 90%. Tahap disseminate memperoleh skor N-Gain 0,56 dengan kriteria "sedang".